(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The integration of artificial intelligence (AI) into education has become a growing topic of interest and study, with the potential to reshape how educational practices are carried out, offering benefits like personalised learning, automated administrative tasks, and immediate feedback. However, implementing AI in education also presents challenges, such as the risk of biased algorithms and concerns about the potential reduction of teachers’ roles in developing critical thinking and creativity in students. This research explores teachers’ views on the use of AI in education through a survey conducted with educators from various academic backgrounds. The results indicate that while many teachers are familiar with AI and see its potential, its use in everyday teaching is still not widespread, and there are mixed feelings about its impact. Teachers value AI for its ability to assist with learning and provide support to students with special needs. However, they also worry that relying too much on technology could negatively affect students’ critical thinking and motivation. The study highlights the importance of carefully integrating AI into education, ensuring that it enhances rather than replaces traditional teaching methods and that any challenges are thoughtfully addressed.